2019
DOI: 10.1002/cam4.2502
|View full text |Cite
|
Sign up to set email alerts
|

Changes in conditional net survival and dynamic prognostic factors in patients with newly diagnosed metastatic prostate cancer initially treated with androgen deprivation therapy

Abstract: Background The purpose of this study was to identify predictive factors associated with conditional net survival in patients with metastatic hormone‐naive prostate cancer (mHNPC) initially treated with androgen deprivation therapy (ADT). Methods At nine hospitals in Tohoku, Japan, the medical records of 605 consecutive patients with mHNPC who initially received ADT were retrospectively reviewed. The Pohar Perme estimator was used to calculate conditional net cancer‐specific survival (CSS) and overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…14 Furthermore, Narita et al showed improved conditional CSS and OS in patients with metastatic prostate cancer in Japan. 16 In a similar manner, the present study showed that conditional OS in stage IV and high-risk patients as per the J-CAPRA system have improved over time. In patients with advanced and high-risk disease, high mortality from prostate cancer in patients with poor prognosis might explain the reason for consistent improvement in conditional CSS and OS.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…14 Furthermore, Narita et al showed improved conditional CSS and OS in patients with metastatic prostate cancer in Japan. 16 In a similar manner, the present study showed that conditional OS in stage IV and high-risk patients as per the J-CAPRA system have improved over time. In patients with advanced and high-risk disease, high mortality from prostate cancer in patients with poor prognosis might explain the reason for consistent improvement in conditional CSS and OS.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, Narita et al reported unchanged prognostic impact of disease extent on bone in metastatic prostate cancer, the parameter that was not unavailable in the present study. 16 The findings in the present study showed several clinical implications. There was gradual improvement in the survival over time; therefore, de-escalation of treatment in patients with reduced risk might be considered.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Despite getting increased popularity in healthcare [35][36][37][38][39][40], to our knowledge this is the first time the technique presented in this paper has been used for dynamic modelling of the performance of real-time Healthcare 4.0 alerting systems, as well as for the indirect evaluation of the quality of received care.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested the role of glycans as potential biomarkers for diseases (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). A broad range of glycan alterations have been observed in blood-based or tissuebased analysis, including aberrant PSA glycosylation, increased sialylation, core fucosylation, O-GlcNAcylation, and branched N-glycan formation (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71).…”
Section: Introductionmentioning
confidence: 99%